158k views
2 votes
Solve the Law of Cosine: c^2 = a^2+ b^2 - 2abcosC for cos C.

Solve the Law of Cosine: c^2 = a^2+ b^2 - 2abcosC for cos C.-example-1

2 Answers

6 votes

Answer:

a on ed

Explanation:

User Fooquency
by
5.3k points
4 votes

Answer:

The Law of Cosine : cos C =
(a^(2)+ b^(2)-c^(2))/(2ab)

Explanation:

See the figure to understand the proof :

Let A Triangle ABC with sides a,b,c,

Draw a perpendicular on base AC of height H meet at point D

Divide base length b as AD = x -b and CD = x

By Pythagoras Theorem

In Triangle BDC And In Triangle BDA

a² = h² + x² ( 1 ) c² = h² + (x-b)²

c² = h² + x² + b² - 2xb ...(. 2)

From above eq 1 and 2

c² = (a² - x²) + x² + b² - 2xb

or, c² = a² + b² - 2xb .....(3)

Again in ΔBDC

cos C =
(BD)/(BC)

Or, cos C =
(x)/(a)

∴ x= a cos C

Now put ht value of x in eq 3

I.e, c² = a² + b² - 2ab cos C

Hence , cos C =
(a^(2)+ b^(2)-c^(2))/(2ab) Proved Answer

Solve the Law of Cosine: c^2 = a^2+ b^2 - 2abcosC for cos C.-example-1
User Dasari Kamali
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.